A MASS-BALANCE TROPHIC FLOW MODEL AT AWUR BAY IN THE NORTHERN CENTRAL JAVA SEA - Muhammad Zainuri; Hadi Endrawati (JOURNAL OF COASTAL DEVELOPMENT, 1999)
A mass-balance trophic flow model is constructed using a simple model termed ECOPATH. The model is applied to an ecosystem at Awur bay, Jepara in the northern central Java sea. The model constructed was built based on twelve components of the ecosystem, which were partitioned into groups of similar species and provide for these species groups, estimates of production biomass, diet and food consumption. Three tropic level of the components were clearly presented in the model. A number of the estimates mean biomass was 3922.054 gC.m-2.yr-1, while net primary production was 78439.48 gC.m-2.yr-1, over 115 ha area at Awur bay, northern coast of Central Java.